2016
DOI: 10.1093/nar/gkw154
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into DNA sequence recognition by Type ISP restriction-modification enzymes

Abstract: Engineering restriction enzymes with new sequence specificity has been an unaccomplished challenge, presumably because of the complexity of target recognition. Here we report detailed analyses of target recognition by Type ISP restriction-modification enzymes. We determined the structure of the Type ISP enzyme LlaGI bound to its target and compared it with the previously reported structure of a close homologue that binds to a distinct target, LlaBIII. The comparison revealed that, although the two enzymes use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…The cleavage data show that linear DNA with a pair of sites in direct repeat (HtT1 or HtT2) is the most efficiently cut, where cleavage dominates at the second site (downstream to the first as drawn in Figure 4 ), with a rate that is similar to that of the one-site circular DNA and which is independent of local sequence (∼10 −3 s −1 , Supplementary Table S3 ). This would be consistent with a rear-end collision mechanism for activation of cleavage that is different from the Type I, ISP and III RM enzymes ( 5 , 16 , 20 , 22 , 40 , 41 ). However, we also observed cleavage of both DNA with sites in inverted repeat (HtH and TtT) with a similar rate (∼10 −4 s −1 ) that is 10-fold slower than the direct repeats (Figure 4B and Supplementary Table S3 ).…”
Section: Resultssupporting
confidence: 71%
“…The cleavage data show that linear DNA with a pair of sites in direct repeat (HtT1 or HtT2) is the most efficiently cut, where cleavage dominates at the second site (downstream to the first as drawn in Figure 4 ), with a rate that is similar to that of the one-site circular DNA and which is independent of local sequence (∼10 −3 s −1 , Supplementary Table S3 ). This would be consistent with a rear-end collision mechanism for activation of cleavage that is different from the Type I, ISP and III RM enzymes ( 5 , 16 , 20 , 22 , 40 , 41 ). However, we also observed cleavage of both DNA with sites in inverted repeat (HtH and TtT) with a similar rate (∼10 −4 s −1 ) that is 10-fold slower than the direct repeats (Figure 4B and Supplementary Table S3 ).…”
Section: Resultssupporting
confidence: 71%
“… Comparison of the helicase-like domains of Types I, ISP and III restriction enzymes. Helicase consensus motifs are shown based on the work here and ( 61 , 78 , 80 , 81 ). The Type IIIA consensus sequences are presented.…”
Section: Resultsmentioning
confidence: 99%
“…For the TaqII branch of the Thermus -family enzymes we currently have just three proteins for which the recognition motif is known. However the TRDs of TaqII and TaqIII have significant similarity to the TRDs of the Type ISP enzymes LlaGI and LlaBIII, for which crystal structures have recently been determined and residues making direct DNA contacts have been identified ( 42 ) ( Supplementary data, Figure S6 ). We therefore aligned TaqII, TaqIII and TspGWI with the Type ISP enzymes described by Kulkarni, et al ( 42 ), and find that the TaqII and TaqIII proteins match well with the observed and co-variation-predicted DNA recognition elements in the Type ISP enzymes (Figure 8 ; Supplementary data, Figure S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…However the TRDs of TaqII and TaqIII have significant similarity to the TRDs of the Type ISP enzymes LlaGI and LlaBIII, for which crystal structures have recently been determined and residues making direct DNA contacts have been identified ( 42 ) ( Supplementary data, Figure S6 ). We therefore aligned TaqII, TaqIII and TspGWI with the Type ISP enzymes described by Kulkarni, et al ( 42 ), and find that the TaqII and TaqIII proteins match well with the observed and co-variation-predicted DNA recognition elements in the Type ISP enzymes (Figure 8 ; Supplementary data, Figure S6 ). Note that in this discussion of recognition elements, we present the TaqII/TaqIII strand that contains the adenine which the enzymes methylate, and refer to the base positions as 0, 1, 2, 3, 4, 5 (and 6), where the fifth position is the methylated adenine, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation